THE EFFECT OF AUDITOR COMPETENCE, INDIVIDUAL MORALITY AND THE EFFECTIVENESS OF THE INTERNAL CONTROL SYSTEM ON FRAUD PREVENTION AT MEDAN CITY PUBLIC ACCOUNTING FIRM - Indri Julieta Br Ketaren; Tuti Meutia; Agustina Nurul Fajriah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine the influence of Auditor Competence, Individual Morality and the Effectiveness of the Internal Control System on Fraud Prevention at Medan City Public Accounting Firm. The sample selection in this study is to use a saturated sample model using the entire population into a sample. The total population in this study is 48 senior auditors from 22 Public Accounting Firms (KAP) located in Medan City. Data collection was carried out by distributing questionnaires to 48 respondents. The data obtained were analyzed using the SPSS (Statistical Product and Service Solutions) program. The analytical methods used in this study are validity test, classical assumption test and multiple linear regression analysis. The results of this study show that (1) Auditor Competence does not have a significant effect on fraud prevention. (2) Individual morality partially has a significant influence on fraud prevention. (3) The effectiveness of the Internal Control System does not have a significant effect on fraud prevention and (4) Auditor Competence, Individual Morality and Internal Control System Effectiveness simultaneously have a significant influence on fraud prevention.